Hubungan Antara Self Efficacy dan Coping Stress pada Mahasiswa yang Bekerja di Universitas X - Mochammad Dzacky Danial; Yohana Wuri Satwika (Arbain Publishing, 2025)
This study investigates the relationship between self-efficacy and coping stress among working students at University X. Using a quantitative research design, the data analysis was carried out through the Pearson Product Moment correlation. The study involved 95 active students who are balancing both work and studies at University X in Surabaya. The results of the analysis revealed a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.731 (r = 0.731). These findings indicate a strong positive correlation between self-efficacy and coping stress, meaning that as self-efficacy increases, students’ ability to manage stress improves. This suggests that students with higher confidence in their capabilities are more effective in using coping strategies to deal with the pressures of both work and academic responsibilities. The study emphasizes the importance of enhancing self-efficacy as a means of helping working students manage stress, highlighting the critical role of personal belief in overcoming challenges in both academic and work settings. The significant relationship found in this study contributes to understanding how self-efficacy can serve as a vital factor in developing better stress management strategies among working students.